Corporate Governance, Financial Structure and Sustainable Social Responsibility with the Profitability of Listed Companies in the Stock Exchange of Thailand, Resource Group (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims to study corporate governance, financial structure and sustainable social responsibility with the profitability of listed companies in the Stock Exchange of Thailand, Resource Group. Secondary data from financial statements and information disclosure forms (Form 56-1) from 2021 to 2023, 73 companies, were analyzed using descriptive statistics, correlation and multiple regression. The results of the research found that corporate governance for the number of board of directors, the proportion of independent directors, the executive power of the chairman, the number of board meetings of the company per year, the total debt to equity ratio were positively related to the profitability, namely, the return on total assets, the return on equity ratio and the gross profit margin, with statistical significance at the 0.01 and 0.05 levels, and social responsibility, namely, the company’s social responsibility activities, the environmental disclosure score, were positively related to the profitability, namely, the return on total assets, the return on equity ratio and the gross profit margin, with statistical significance at the 0.01 and 0.0 levels.